К.МАМБЕТОВТЫҢ «ПОСҚАН ЕЛ» РОМАНЫНДА ГИДРОНИМЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Мамбетова, Г. (FAN va JAMIYAT, 2016)
The article deals with the role of hydronyms in the novel «Posqan el» by K.Mambetov and use of hydronyms is explained on the scientific basis. Some hydronyms are used to express the living places of personages and heroes in literary language. In the article there have been analyzed semantics of names of earlier water objects in Kungrad ruled by beks.